2013
DOI: 10.1111/jgs.12359
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Perspectives on Cancer Screening for Persons with Dementia: “Why Put Them Through It?”

Abstract: Objectives To describe the perspectives of family caregivers toward stopping cancer screening tests for their relative with dementia and identify opportunities to reduce harmful or unnecessary screening. Design Focus group study Setting Alzheimer’s Association support groups for family members of patients with dementia. Participants Four focus groups including 32 caregivers with mean age 65.5 years (range 49–85 years). There were 25 women; 24 were white, 7 African American and 1 African American/Indian. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…This requires education founded on the EAPC's 11 domains of best practice in palliative care provision for people with dementia and their family carers (van der Steen et al., ). There is also evidence from a Canadian study that healthcare professionals who are able to demonstrate knowledge and expertise can more effectively initiate discussion and facilitate decision‐making with family carers of people with dementia (Torke, Schwartz, Holtz, Montz, & Sachs, ). Additionally, it is known that family carers need a whole family approach to consult with and be reassured following a best interest decision (Livingston et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This requires education founded on the EAPC's 11 domains of best practice in palliative care provision for people with dementia and their family carers (van der Steen et al., ). There is also evidence from a Canadian study that healthcare professionals who are able to demonstrate knowledge and expertise can more effectively initiate discussion and facilitate decision‐making with family carers of people with dementia (Torke, Schwartz, Holtz, Montz, & Sachs, ). Additionally, it is known that family carers need a whole family approach to consult with and be reassured following a best interest decision (Livingston et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of dementia could lead relatives to give higher priority to quality of life over life expectancy, to recognize the palliative nature of the situation, and to thus to reconsider the benefit of anticancer treatments for the individual . Studies conducted in nursing homes have, for instance, shown that relatives of older adults with dementia are less likely to request invasive life‐sustaining treatments . Finally, physicians might be more reluctant to prescribe aggressive treatments to individuals with cancer near the end of life when they have dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Carers report a shift in the dynamic to a "mother/child" type relationship and Table 4. Summary of triggers, barriers, and facilitators to decision-making (Butcher et al, 2001;Ducharme et al, 2012) Desire to honor person with dementia's wishes (Elliott et al, 2009) Family and professionals perspectives (Livingston et al, 2010;Ducharme et al, 2012) Carer unable to cope and care/ deterioration in carer health (Cohen et al, 1993;Caron et al, 2006;Ducharme et al, 2012) Emotional impact (anguish, burden guilt) (Butcher et al, 2001;Livingston et al, 2010) Support from others once decision made (Butcher et al, 2001) Change in living environment (Caron et al, 2006) Resistance from person with dementia (Livingston et al, 2010;Chrisp et al, 2012;Wolfs et al, 2012;Chrisp et al, 2013) Relationship to person with dementia (Wackerbarth, 1999) Person with dementia's ability to make decisions (Caron et al, 2006) Barriers to accessing services/lack of support/information (Wackerbarth, 1999;Butcher et al, 2001;Livingston et al, 2010) Adapting caring role following a decision (Kwon and Tae, 2012) Cultural treachery and distress (Chang and Schneider, 2010;Chang et al, 2011;Kwon and Tae, 2012) Collaborating with healthcare professionals (Walker and Dewar, 2001;Heinrich et al, 2003;Torke et al, 2013) Role change to "mother/child" (Cairns, 2012) Mild to moderate dementia severity (Smebye et al, 2012) Knowing when the "right" take to ...…”
Section: Role Transitions and Perceptionsmentioning
confidence: 99%
“…Collaborating with staff helped carers with the process of deciding when to place their relative into a care home (Heinrich et al, 2003) and where carers felt involved in decision-making, this was facilitated by a trusted healthcare professional who consulted them and advocated effectively (Walker and Dewar, 2001). Torke et al (2013) asked a focus group of USA carers about decision-making around cancer screening for people with dementia. Carers felt that clinician's raising discussion around this decisionmaking and being expert and knowledgeable helped them with the decision-making process.…”
Section: Facilitators To Decision-makingmentioning
confidence: 99%